Properdin, transcortin and HGFAC are novel plasma biomarkers in canine chronic inflammatory enteropathies from active disease to remission - Pavlos G. Doulidis; Carolina Frizzo Ramos; Alexandro Rodriguez-Rojas; Franziska Roth-Walter; Iwan A. Burgener (Scientific Reports)
Abstract Canine chronic inflammatory enteropathies (CCIE) is a group of intestinal inflammatory conditions causing chronic or relapsing gastrointestinal symptoms. Accurate diagnosis, treatment and monitoring remain challenging, necessitating novel diagnostic tools. This study aims to investigate the plasma proteome of ten dogs with histologically confirmed CCIE during active disease and clinical remission compared to ten healthy controls. We utilized surplus lithium-heparin plasma and performed label-free quantification mass spectrometry. A significant upregulation of complement factor properdin (CFP) during disease was noted, pointing toward microbial-driven intestinal inflammation. During remission, CFP levels remained elevated compared to controls, indicating persistent subclinical inflammation. We report hepatocyte growth factor activator (HGFAC) as a novel canine plasma protein associated with decreased risk for CCIE and as a potential therapeutic target, similarly, as reported in humans. Linear regression analysis revealed that disease severity was negatively correlated to transcortin/SERPINA6, as negative acute phase protein. Proteins involved in inflammation and tissue repair, such as inter-alpha-trypsin inhibitor heavy chain 4, (ITIH4), and anti-inflammatory molecules like apolipoprotein A-IV (APOA4), were significantly upregulated in remission. Conversely, proteins related to DNA remodeling and methylation, including histone H2B and carboxypeptidase N subunit 2 (CPN2), were downregulated during remission. Gene ontology analysis revealed altered pathways linked to immune response and coagulation. In CCIE patients we identified for the first time markers such as properdin for intestinal inflammation, while transcortin and HGFAC may serve as markers for remission. Future studies with larger cohorts are needed to validate the use of these proteins for monitoring disease progression and remission and refine their clinical applicability.